1985
DOI: 10.1515/znc-1985-5-607
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Terpenoids from the Leaf Resin of Pluchea odorata

Abstract: The chemical composition of the leaf resin of Pluchea odorata has been studied from material collected in Tamaulipas, Mexico. It mostly consists of triterpenes and phytosterols and an eudesmane type sesquiterpene. Very small amounts of ten different flavonol aglycones occur, dissolved in this resin; most of them are 6-methoxy compounds. A comparison with previous results on material from El Salvador shows that the latter contains a lesser number of triterpenes and especially of flavonoids, but more sesquiterpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Both mechanisms were overlapping at the time-points measured (and cannot be dissected by differently scheduled timing) and this allows the conclusion that the dichloromethane extract of P. odorata harbours an extraordinaryly potent pro-apoptotic activity, which can be exploited for the development of an anti-cancer therapeutical approach. Pluchea species were shown to contain polyphenols, terpenoids and flavonoids (28)(29)(30)(31). When tested in HL-60 and other cancer cells, flavonoids and other (poly)phenolic compounds were shown to elicit apoptosis and inhibit the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both mechanisms were overlapping at the time-points measured (and cannot be dissected by differently scheduled timing) and this allows the conclusion that the dichloromethane extract of P. odorata harbours an extraordinaryly potent pro-apoptotic activity, which can be exploited for the development of an anti-cancer therapeutical approach. Pluchea species were shown to contain polyphenols, terpenoids and flavonoids (28)(29)(30)(31). When tested in HL-60 and other cancer cells, flavonoids and other (poly)phenolic compounds were shown to elicit apoptosis and inhibit the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Among polyphenols, flavonoids, and sesquiterpenes there are a plethora of bio-active compounds and studies more than 20 years ago analysed P. odorata regarding its constituents. It was shown that it contains flavonoids, triterpenes (28,29), phytosterols (44), and Plucheinol, an eudesmane type sesquiterpene unique to P. odorata (30,31). A comparison between two P. odorata populations from Mexico and El Salvador showed that the Mexican population contained a greater number of triterpenes and flavonoids, whereas the plants from El Salvador contained a greater number of sesquiterpenes (29,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Several flavonols mainly of the quercetin, kempferol and quercetagetin types have been identified. [15][16][17] In addition,…”
Section: Introductionmentioning
confidence: 99%
“…: Antioxidants from Pluchea carolinensis and Pluchea rosea a few flavonol aglycones have been previously isolated from P. carolinensis, 18 no report from P. rosea and various flavonoids have been identified from P. odorata. 16 In addition, polyphenols including flavonoids have been reported to exhibit a wide range of biological activities and their effects are mainly attributed to the antioxidant properties. 19 As far as we know, the chemical composition of phenolic compounds of the Cuban Pluchea species and thus, the phytochemicals responsible of the antioxidant capacity of the crude extracts are still unknown.…”
Section: Introductionmentioning
confidence: 99%